Hukum dan Demokrasi: Sinergi Negara Hukum dan Partisipasi Warga Negara - Achmad Fauzan Ramadhan (Bahasa Indonesia, 2025)
This study aims to analyze the relationship between the principles of the rule of law and democracy in building a governance system that is fair, participatory, and oriented toward social justice. The focus of the research lies in examining how constitutional supremacy, human rights protection, and public participation can reinforce each other within the framework of a democratic rule of law. The method employed is library research with a normative juridical approach, by reviewing legal literature, constitutional provisions, and academic documents related to democracy. The analysis is carried out descriptively and qualitatively to reveal both the conceptual and practical connections between the rule of law and democracy in Indonesia. The findings show that the rule of law and democracy are inseparable principles. A rule of law without democracy risks creating authoritarianism, while democracy without law may lead to anarchy. Both must be integrated through institutional structures, legal culture, and policy reforms that ensure transparency, accountability, and respect for human rights. Such integration is a prerequisite for realizing a democratic and just government.